The effect of ambient conditions on the impedance spectra of newly synthezised organic semiconductor thin films - (:unkn) unknown (My University, 2007)
A detailed study of the effect of the film preparation conditions on the d.c conductivity and impedance spectra of a newly synthesized trinuclear phthalocyanine (ZnPc) derivative were carried out at the temperatures between 290 K and 420 K. We find that the experimental data are described by thermally activated conductivity dependence on temperature. A quassi-vertical line was observed in Nyquist plot for all films at room temperature. Both the complex impedance and Bode plots showed that the ZnPc coated IDT can be represented by different equivalent circuits as depend on temperature © 2007 American Institute of Physics.
Keywords: Activation energy; Correlated barrier hopping; Impedance spectroscopy; Phthalocyanine